The impact of green finance on the transformation of energy consumption structure: Evidence based on China - Gu, Xiao; Qin, Lingui; Zhang, Mei (Frontiers in Earth Science, 2023)
Reducing the use of traditional fossil energy and optimizing the energy consumption structure is an important starting point for China to balance sustainable and stable economic development, dual carbon goals and energy security. Green finance can help improve the energy consumption structure through providing financial support for green development. Based on this, taking the proportions of coal consumption as the index of energy consumption structure, this paper uses panel data for 30 provinces in China from 2009 to 2019, and analyzes the impact of green finance on energy consumption structure and its mechanism. The results show that the development of green finance in China has significantly improved the energy consumption structure, when considering the endogenous and robustness, the conclusion is still valid. In the mid-western region, green finance plays a greater role in improving the energy consumption structure. With the help of the quantile regression model, it is found that the higher the proportion of coal consumption, the greater the improvement effect of green finance on energy consumption structure. With the help of the threshold model, it is found that when exceeding the threshold value, the improvement effect of green finance on energy consumption structure will decline. Both the market and the government can enhance the role of green finance in optimizing the energy consumption structure. According to the research conclusion, the suggestions for improving the energy consumption structure of green finance are given from the aspects of developing green finance, formulating differentiated green finance development strategies, and encouraging green innovation.